Optimizing social skills of elementary school students through cooperative and collaborative learning approaches - Supratman Supratman; Andi Mariani Ramlan; La Ode Sirad; Ebenezer Bonyah (EduStream: Jurnal Pendidikan Dasar, 2025)
This study explores the implementation of cooperative and collaborative learning in a fourth grade elementary classroom and its contribution to optimizing students social skills. The research employed a descriptive qualitative approach with a case study design. The participants were 25 fourth grade students with diverse academic abilities and backgrounds, supported by the classroom teacher as a key informant. Data were collected through participatory observation, in depth interviews, and limited documentation. The observation focused on group learning activities that reflected cooperation and collaboration, including task distribution, peer discussion, idea exchange, and shared decision making. Data analysis followed the Miles and Huberman qualitative analysis model, covering data reduction, data display, and conclusion drawing. The findings indicate that cooperative learning helped students develop responsibility and structured teamwork through clear roles and individual accountability. Collaborative learning supported the growth of communication skills by encouraging open discussion and active participation. Interview results showed that students felt more comfortable asking questions, sharing opinions, and working with peers during group learning activities. Teachers also reported positive changes in student engagement and social interaction patterns. These results suggest that integrating cooperative and collaborative learning within one learning process supports the development of students social skills in a meaningful classroom context.